Strategic Analysis On The Business Dynamics Of Intel Microprocessor Based Desktop Computers - Beng, Ooi Ghee (2010)
This dissertation explores the birth and evolution of both the personal computing industry and in particular Intel as a corporation. Also, this dissertation investigate the various tools, models, and frameworks utilized by Intel Corporation to understand, analyze, and characterize the corporation and it\'s related ecosystem.